1999
DOI: 10.1096/fasebj.13.8.773
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E in human cancers

Abstract: Regulators of the cell cycle such as cyclin E play an important part in neoplasia. The cyclin E protein forms a partnership with a specific protein kinase. This complex phosphorylates key substrates to initiate DNA synthesis. Cyclin-dependent kinase inhibitors (CKIs) are able to suppress the activity of cyclin E. Various substances (including proteins produced by oncogenic viruses) affect cyclin E directly or indirectly through an interaction with CKIs. These interactions are important in elucidating the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
158
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(165 citation statements)
references
References 99 publications
1
158
0
3
Order By: Relevance
“…Future study is needed to explore whether the other major downstream property of cyclin D1/CDK4, e.g. sequestering the CDK inhibitor p27 Kip1 to trigger cyclin E-initiated Rb-independent S phase entry (Geng et al, 1999;Perez-Roger et al, 1999;Donnellan and Chetty, 1999), is associated with novel tumorigenic mechanisms caused by ampli®ed PIK3CA in cervical cancer development. Not mutually exclusive are the possibilities that, in cervical tumorigenesis, increased PIK3CA and elevated PI 3-kinase activity contribute to other AKT-involved growth-promoting pathways or antiapoptotic signal.…”
Section: Resultsmentioning
confidence: 99%
“…Future study is needed to explore whether the other major downstream property of cyclin D1/CDK4, e.g. sequestering the CDK inhibitor p27 Kip1 to trigger cyclin E-initiated Rb-independent S phase entry (Geng et al, 1999;Perez-Roger et al, 1999;Donnellan and Chetty, 1999), is associated with novel tumorigenic mechanisms caused by ampli®ed PIK3CA in cervical cancer development. Not mutually exclusive are the possibilities that, in cervical tumorigenesis, increased PIK3CA and elevated PI 3-kinase activity contribute to other AKT-involved growth-promoting pathways or antiapoptotic signal.…”
Section: Resultsmentioning
confidence: 99%
“…However, preclinical experiments have shown that the pattern of genetic alterations might determine the success or the failure of such strategies. Overexpression of CycE, together with p27 downregulation, has been related to tumor progression and stage in a number of malignancies like breast, stomach and colorectal cancer, and osteosarcoma (summarized in Donnellan and Chetty 45 ). Moreover, its prognostic value has been described in some of these cases.…”
Section: Discussionmentioning
confidence: 99%
“…In general, we observed parallel expression of Cdk2 with cyclin E, supporting the expected interaction of these two regulators as a complex. Overexpression of cyclin E has been reported in a variety of malignancies, including squamous cell carcinomas of lung and cervix, acute lymphoblastic leukemia, and in gastric adenocarcinoma, especially in deeply invasive tumors (32)(33)(34)(35)(36)(37). Our findings support an important role for cyclin E in the development of GTD, including choriocarcinoma.…”
Section: Discussionmentioning
confidence: 99%